Dampak Motivasi Terhadap Penilaian Kerja Dalam Organisasi - Elsa Dewi Farantika; Dani Nisrina Maulida; Tri Wahyuni Lestari; Elga Yohana Azzahra; Ihza Maisan Ghifari; Advan Nur Widya; Salma Qurratul’ain; Sunarti Sunarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Motivation is a drive that arises within an individual, whether consciously or unconsciously, to perform an action with a specific goal in mind. Motivation at work is closely related to performance evaluation, which reflects the outcomes of tasks carried out by individuals or teams. Performance evaluation is an essential element within an organization that shapes the expectations of each member. With performance evaluation, each individual feels that their efforts and hard work are appreciated by the company. Recognition of job performance achievements serves as a return for the work done and can boost work morale, encouraging employees to work more systematically and enthusiastically towards achieving better results. Therefore, this study aims to understand the impact of motivation on performance evaluation, as well as the relationship between work motivation and work productivity..